The dentist's drug and prescription guide - Weinberg, Mea A.; Froum, Stuart J. (Chichester, West Sussex : Ames, Iowa : John Wiley & Sons, 2012)
& I & The Dentist & rsquo;s Drug and Prescription Guide & /i & is written for dental professionals seeking quick advice on prescribing medications for their patients. Using an easy to read question-and-answer format, & nbsp;the text describes evidenced based pharmacologic therapy with current and up-to-date references regarding adjunctive pharmacologic treatment of the dental patient. Drug therapy for each dental discipline including periodontics, implantology, oral surgery, and endodontics is included, with recommendations for pharmacologic treatment with periodontal and implant surgery as well as.
7. Management of the medically compromised dental patient.
Includes bibliographical references and index.
Print version record.
Keywords: Dental pharmacology -- Handbooks, manuals, etc; Drugs -- Prescribing -- Handbooks, manuals, etc; Drugs -- Dosage -- Handbooks, manuals, etc; Dental pharmacology; Dental pharmacology -- Handbooks, manuals, etc; Drugs -- Dosage; Drugs -- Dosage -- Handbooks, manuals, etc; Drugs -- Prescribing; Drugs -- Prescribing -- Handbooks, manuals, etc; HEALTH & FITNESS -- Oral Health; MEDICAL -- Dentistry -- General; Dental pharmacology; Drugs -- Dosage; Drugs -- Prescribing; Pharmacological Preparations, Dental -- pharmacology -- Handbooks; Pharmacological Preparations, Dental -- administration & dosage -- Handbooks; Pharmacological Preparations, Dental -- adverse effects -- Handbooks; Electronic books; Handbooks and manuals; Electronic books